ANALISIS SENTIMEN KOMENTAR PADA POSTINGAN INSTAGRAM AKUN “STANDWITHUS” MENGGUNAKAN KLASIFIKASI NAIVE BAYES - Khairunnisa, Khairunnisa; Dewi, Shanty Kurnia; Rahmawati, Deisya Dzakiyyah; Sari, Anggraini Puspita (LPPM Universitas Putera Batam, 2024)
Social media platforms like Instagram play a crucial role in shaping public opinion and fostering community engagement in the digital age. The